The Influence of Accounting Literacy and Financial Attitude on Generation Z’s Financial Management Behavior in Pangkalan Kerinci, Pelalawan Regency - Putri Diyah Makarti Desi (Sosial Budaya, 2024)
The purpose of this study is to examine how accounting literacy and financial attitudes affect Generation Z's financial management practices in Pangkalan Kerinci, Pelalawan Regency. The study employs an associative research design and a quantitative methodology. Purposive sampling was used to choose the 80 respondents that made up the research sample. Likert-scale questionnaires were used to collect data, and interviews were used to confirm the results. Multiple linear regression with t-test, F-test, and coefficient of determination (R2) was utilized in the data analysis. The study's findings indicate that financial attitude has a positive and significant impact on financial management behavior with a significance value of 0.000 < 0.05 and accounting literacy has a positive and significant impact with a significance value of 0.001 < 0.05. have a considerable impact on financial management practices as well, with a significance value of 0.000 < 0.05. Accounting literacy and financial attitude account for 64.2% of the variation in financial management behavior, whereas other factors outside the research account for 35.8%, according to the Adjusted R Square value of 0.642. The findings of the interviews indicate that even while Generation Z has recognized the need of sound financial management, issues like a consumerist lifestyle and the impact of digital trends continue to influence their financial conduct. According to the study's findings, encouraging a good financial mindset and raising accounting literacy are crucial elements in improving Generation Z's financial management practices.